2019
DOI: 10.3389/fpsyg.2019.01902
|View full text |Cite
|
Sign up to set email alerts
|

Empathy Impairment in Individuals With Autism Spectrum Conditions From a Multidimensional Perspective: A Meta-Analysis

Abstract: Background: Although empathy has always been considered to be impaired in individuals with autism spectrum conditions (ASCs), the relevant findings have been inconsistent. The present meta-analysis aims to determine which empathy components are impaired and how culture, gender, and age moderate such empathy impairment.Methods: By using “Autism,” “Asperger Syndrome,” “Empathy,” and related Chinese synonyms as keywords, we searched the databases of Weipu, Wanfang, CNKI, Web of Science, Science Direct, SpringerLi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 151 publications
2
46
0
Order By: Relevance
“…This hypothesis should be tested by comparing "pure" ASD and ODD/CD with patients with ADHD and comorbidity conditions. Interestingly, recent studies shed some light on future research about specific empathy impairments in ASD and ODD/CD individuals, suggesting that different mechanisms and factors may be involved in empathic problems in such conditions [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis should be tested by comparing "pure" ASD and ODD/CD with patients with ADHD and comorbidity conditions. Interestingly, recent studies shed some light on future research about specific empathy impairments in ASD and ODD/CD individuals, suggesting that different mechanisms and factors may be involved in empathic problems in such conditions [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated heightened empathy in siblings of children with ASD (e.g., McDonald et al, 2017;Shivers, 2019), suggesting that some siblings may benefit from their experiences of having a brother or sister with ASD, and develop understanding and compassion. Intact empathic abilities in siblings of children with ASD suggest that the presence of more autistic traits on a group level does not necessarily include deficits in empathy like those characteristic of ASD (Harmsen, 2019;Song et al, 2019). However, future studies should examine whether levels of autistic traits and empathy are related in siblings.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with ASD display lower scores on conventional measures of empathy and prosocial behavior (Harmsen, 2019;Russell et al, 2012;Song et al, 2019). Some studies have found that individuals with ASD primarily display difficulties with cognitive empathy, whereas affective empathy appears to be comparable with that of TD individuals (e.g., Deschamps et al, 2014;Rogers et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ]). In addition, we note that definitions of ‘theory of mind' are not consistently agreed-upon and ‘theory of mind’ tests often tap related constructs such as emotion perception, figurative language comprehension and empathy; with the exception of figurative language, meta-analyses provide support for average differences between autistic and non-autistic people in some aspects of these other constructs (see [ 8 , 10 , 11 ]). In addition to a difference on the ‘social understanding' factor, we hypothesized that there would be no difference on ‘core language' factor between autistic and non-autistic groups, as structural language impairments are not a core feature of autism [ 1 ].…”
Section: Introductionmentioning
confidence: 99%